2015
DOI: 10.1186/s12916-015-0537-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the free radical/oxidative stress theory of ageing from the CHANCES consortium: a meta-analysis of individual participant data

Abstract: BackgroundThe free radical/oxidative stress theory of ageing has received considerable attention, but the evidence on the association of oxidative stress markers with mortality is sparse.MethodsWe measured derivatives of reactive oxygen metabolite (D-ROM) levels as a proxy for the reactive oxygen species concentration and total thiol levels (TTL) as a proxy for the redox control status in 10,622 men and women (age range, 45–85 years), from population-based cohorts from Germany, Poland, Czech Republic, and Lith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
80
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 41 publications
8
80
0
6
Order By: Relevance
“…For instance, in a study among 48 male healthy candidates for military service in Macedonia (mean age 25 years), Jansen et al [16] found that d-ROM levels were 14% higher in smokers compared with non-smokers, whilst such differences were not observed for TTL. In agreement with this finding, a meta-analysis of individual participant data from 4 large cohort studies showed that, compared to never smokers, former smokers had a statistically significant 1.15-fold increased odds of high OS defined by d-ROM levels [400 Carr U and current smokers had 1.62-fold increased odds, whereas no association was observed between smoking and TTL [4]. Moreover, Montuschi et al and Kinnula et al found 8-iso to be a biomarker OS in the lungs.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…For instance, in a study among 48 male healthy candidates for military service in Macedonia (mean age 25 years), Jansen et al [16] found that d-ROM levels were 14% higher in smokers compared with non-smokers, whilst such differences were not observed for TTL. In agreement with this finding, a meta-analysis of individual participant data from 4 large cohort studies showed that, compared to never smokers, former smokers had a statistically significant 1.15-fold increased odds of high OS defined by d-ROM levels [400 Carr U and current smokers had 1.62-fold increased odds, whereas no association was observed between smoking and TTL [4]. Moreover, Montuschi et al and Kinnula et al found 8-iso to be a biomarker OS in the lungs.…”
Section: Introductionsupporting
confidence: 52%
“…The free radical/oxidative stress theory of aging suggests that an increased production of reactive oxygen species (ROS) contribute to the developments of age-related diseases, including various forms of cancer, cardiovascular diseases, cognitive decline, as well as increased all-cause mortality [1][2][3][4]. Oxidative stress (OS) occurs when ROS cannot be balanced by anti-oxidative capacities of tissues and has been primarily suggested to be an important contributor to the accelerated senescence of cells and accelerated aging [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we demonstrate that 8‐oxo‐2′‐dG, a marker of oxidative damage, is independently associated with all‐cause mortality and cardiovascular mortality in adults with longstanding type 2 diabetes mellitus who participated in the ADVANCE trial. This finding is consistent with smaller observational studies linking survival of patients with diabetes mellitus to other markers of oxidative stress, including oxidized RNA,10, 11 derivatives of reactive oxygen metabolite,19 advanced autoxidation products,2, 20 and F‐isoprostanes 2, 20. However, this is the first large prospective study to confirm an independent association between mortality and 8‐oxo‐2′‐dG in type 2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 89%
“…Дисбаланс цих проміжних продуктів обміну речовин призводить до такого відомого феномену, як оксидативно-нітрозативний стрес, за якого вільні радикали можуть пошкоджувати різні біомолекули, призводячи до порушень функ-ції різних органів та їх систем. У тканинах серцево-судинної системи він є характерним для старих організмів і, як наслідок, вільно-радикальна теорія старіння є домінуючою протягом багатьох років [1,2]. Вирішальна роль вільнорадикальних впливів відводиться і в розвитку таких хвороб похилого віку, як гіпертензія, діабет, атеросклероз, серцева не-достатність, паркінсонізм тощо [3,4].…”
unclassified